2012
DOI: 10.1007/s12185-012-1159-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum granulysin and its clinical relevance in mature NK-cell neoplasms

Abstract: Mature natural killer (NK)-cell neoplasms include extranodal NK/T cell lymphoma, nasal type (ENKL), aggressive NK-cell leukemia (ANKL) and chronic lymphoproliferative disorders of NK cells (CLPD-NK). Granulysin, a cytolytic granule protein, is expressed in cytotoxic T cells and NK cells, and is found in the sera as well, and functions as a cytotoxic and proinflammatory protein. Cytolytic proteins, such as granzyme B and perforin, have been shown to play crucial pathophysiological roles in NK/T cell neoplasms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Accordingly, we found that the highest level (score 3) of granulysin expression was in a subset of ENKTLs (71%) and higher when compared to that of other cytotoxic markers ( p  < 0.01). This finding supported the results of a previous investigation that reported elevated serum levels of granulysin in patients with NK/T cell lymphoma [8]. In the present study, we are not able to quantify serum levels of granulysin from blood samples and to correlate with its expression in tumour tissue.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Accordingly, we found that the highest level (score 3) of granulysin expression was in a subset of ENKTLs (71%) and higher when compared to that of other cytotoxic markers ( p  < 0.01). This finding supported the results of a previous investigation that reported elevated serum levels of granulysin in patients with NK/T cell lymphoma [8]. In the present study, we are not able to quantify serum levels of granulysin from blood samples and to correlate with its expression in tumour tissue.…”
Section: Discussionsupporting
confidence: 89%
“…Expression of granulysin in normal and neoplastic lymphoid tissues has been only rarely characterised [8]. In the current study, we show that granulysin is expressed in cytotoxic/NK lymphocytes and in subsets of NK/T cell derived lymphomas.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Granulysin is physiologically expressed in activated T cells, NK cells [27,28], and natural killer T (NKT) [29] cells. Both mediators, perforin and granulysin have been shown to play crucial pathophysiological roles in NK/T cell neoplasms, and have also been utilized for diagnostic purposes [30]. The mature form of granulysin (9 kDa) uses multiple mechanisms for target cell killing [27,28].…”
Section: Introductionmentioning
confidence: 99%